Metastatic low-grade endometrial stromal sarcoma of uterus presenting as a primary pancreatic tumor: case presentation and literature review - Aoife J. McCarthy; Blaise A. Clarke; Ian McGilvray; Brendan C. Dickson; Korosh Khalili; Runjan Chetty (BMC, 2019)
Abstract Background Metastatic tumors to the pancreas are uncommon, accounting for approximately 2% of pancreatic malignancies. The most common primary tumors to give rise to pancreatic metastases are carcinomas. Case presentation A 50-year old female patient was investigated for a cause of abdominal discomfort. She had a 2-year history of menorrhagia and dysmenorrhea which was ascribed to a fibroid uterus. On imaging, she was found to have a large solid and cystic mass in the tail of the pancreas. Imaging also confirmed a fibroid uterus. A distal pancreatectomy and splenectomy showed a 9 cm circumscribed mass within, and grossly confined to, the parenchyma of the pancreatic tail. Microscopically, the pancreatic lesion was lobulated, and well-circumscribed, but focally infiltrative. It comprised sheets of uniform spindled to epithelioid cells with round to oval nuclei, coarse to vesicular chromatin, visible nucleoli, nuclear grooves and clear to eosinophilic cytoplasm. Prominent arterioles were identified. The stroma was collagenized in areas. Occasional hemosiderin-laden macrophages were seen, and focal cystic change was present. There was no evidence of nuclear pleomorphism, mitotic activity or necrosis, and there was no evidence of endometriosis despite multiple sections being taken. Immunohistochemistry showed that the tumor cells were positive for CD10, estrogen receptor (ER), progesterone receptor (PR), Wilms tumor-1 (WT-1) and smooth muscle actin (SMA). RNA sequencing detected a PHF1 rearrangement. The morphological, immunohistochemical and molecular features were of a low-grade endometrial stromal sarcoma (LG-ESS). Subsequent total hysterectomy and bilateral salpingo-oophorectomy 3 months later, showed uterine fibroids and a 5 cm low-grade endometrial stromal sarcoma confined to the uterus, with lymphatic invasion. Conclusions To the best of our knowledge, this is the first documented case of metastatic endometrial stromal sarcoma of uterus presenting as a primary pancreatic neoplasm. An unexpected extra-uterine location and unusual presentation of ESS may make the diagnosis challenging, despite classic histological features. Morphological, immunohistochemical and molecular findings must be combined to render the correct diagnosis.